2017
DOI: 10.1055/s-0037-1604264
|View full text |Cite
|
Sign up to set email alerts
|

Waugh's Syndrome: Report of Two Children with Intussusception

Abstract: Waugh's syndrome (WS) is the rare association of intussusception and intestinal malrotation. We present two such cases in a 5-month-old infant and a 9-year-old girl. Both patients presented with intussusception and were diagnosed with malrotation during workup and surgical exploration. We conclude that the possibility of intestinal malrotation must be taken into consideration while managing children with intussusception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The exact frequency of Waugh's syndrome is not known [7]. However, in their prospective study, Brereton et al reported an atypically positioned duodeno-jejunal junction in 40% of patients with intussusception [2].…”
Section: Discussionmentioning
confidence: 99%
“…The exact frequency of Waugh's syndrome is not known [7]. However, in their prospective study, Brereton et al reported an atypically positioned duodeno-jejunal junction in 40% of patients with intussusception [2].…”
Section: Discussionmentioning
confidence: 99%
“…In rarer cases of retrograde intussusception, retraction attempts to retrieve a migrated catheter, similar to a fishing rod, can result in intussusception of the distal bowel into the proximal bowel and cause retrograde intussusception, as in our patient [ 3 ]. While the etiology of intussusception in the pediatric population is mostly idiopathic, secondary intussusception can occur due to a variety of etiological factors [ 12 , 13 ]. The inclusion of feeding catheter migration as a rare cause of secondary intussusception in children will be helpful for early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Waugh's syndrome is a rare syndrome in which patients present with combined disease pathologies of acute-onset intussusception and gut malrotation. Its incidence has not truly established, but less than 100 cases worldwide have been reported so far as of 2017 [6] . Chronic intussusception constitutes about 3% of all intussusception cases in children less than 1 year and around 10% is older children [7] .…”
Section: Discussionmentioning
confidence: 99%